Protective effect of TM6 on LPS-induced acute lung injury in mice - Xiaoyu Hu (Nature Portfolio, 2017)
Abstract Acute lung injury (ALI) is an acute failure of the respiratory system for which effective treatment is urgently necessary. Previous studies found that several peptides potently inhibited the production of cytokines induced by lipopolysaccharide (LPS). In this study, we synthetized a cell-permeable TIR domain-derived decoy peptide (TM6) and examined its substance for the ability to inhibit TLR signaling in the model of ALI induced by LPS. We demonstrated that TM6 (2.5, 5 and 10 nmol/g) alleviated the histological changes in the lung tissues as well as myeloperoxtidase (MPO) activity, lung W/D ratio, the production of TNF-α, IL-1β and IL-6 induced by LPS. Furthermore, the numbers of total cells, neutrophils and macrophages in the BALF were suppressed by TM6. In vitro, TM6 (5, 10 and 20 µM) inhibited the production of TNF-α, IL-1β and IL-6 in LPS-stimulated alveolar macrophages. Moreover, the activation of Nuclear factor-kappaB (NF-κB) and Mitogen activated protein kinases (MAPK) signaling pathways induced by LPS were also inhibited by TM6. Collectively, our results suggested that TM6 was an effective inhibitor of ALI induced by LPS, and this peptide may very well serve as a future treatment for ALI.